2008
DOI: 10.1890/06-1768.1
|View full text |Cite
|
Sign up to set email alerts
|

GEOMORPHOLOGICAL CONTROLS OFFRAXINUS EXCELSIORGROWTH AND REGENERATION IN FLOODPLAIN FORESTS

Abstract: Geomorphological changes can alter river hydrology and thus influence floodplain forest growth and regeneration. In this paper we quantify the effect of changes in channel elevation at the scale of four decades on hydrological conditions, overbank sediment deposits, water availability, and their impacts on common ash (Fraxinus excelsior) growth and recruitment in floodplain forests of the Ain River, France. Ash is a drought-sensitive species, and its regeneration is influenced by flood disturbance. We compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 58 publications
(69 reference statements)
2
44
0
4
Order By: Relevance
“…Wardle (1961) has shown that Fraxinus is intolerant to water shortages in waterlogged sites where the roots are unable to penetrate deeply. This is in accordance with results obtained by Dufour and Piégay (2008) while investigating growth and regeneration of Fraxinus in floodplain forests.…”
Section: Growth Of Fraxinussupporting
confidence: 93%
“…Wardle (1961) has shown that Fraxinus is intolerant to water shortages in waterlogged sites where the roots are unable to penetrate deeply. This is in accordance with results obtained by Dufour and Piégay (2008) while investigating growth and regeneration of Fraxinus in floodplain forests.…”
Section: Growth Of Fraxinussupporting
confidence: 93%
“…Threshold behaviour is also discussed in the context of the long-term development of soil structures and landforms (Newson and Newson, 2000;Phillips, 2004Phillips, , 2006, fluvial morphology (Willgoose et al, 1991a(Willgoose et al, , 1991bGrant, 1997;Piégay et al, 2000;Fryirs et al, 2007;Harnischmacher, 2007), rill and gully erosion (Bull and Kirkby, 1997;Kirkby et al, 2003;Poesen et al, 2003;Shao et al, 2005;Parkner et al, 2006Parkner et al, , 2007, badlands formation (CalvoCases and Harvey, 1996;Howard, 1997;Faulkner et al, 2000Faulkner et al, , 2003Boardman et al, 2003;Faulkner, 2008), and formation and growth of channel networks (Willgoose et al, 1991a(Willgoose et al, , 1991bRinaldo et al, 1996;Rodriguez-Iturbe et al, 1998;Rodriguez-Iturbe and Rinaldo, 2001). Threshold behaviour and feedbacks between vegetation patterns and redistribution of abiotic resources determine the resilience of geoecosystems in semi-arid regions (Grant, 1997;Piégay et al, 2000;Wilcox et al, 2003a;Wilcox and Newman, 2005;Fryirs et al, 2007;Saco et al, 2007;Tietjen and Jeltsch, 2007), grassland establishment (Baer et al, 2005;Baer and Blair, 2008), regeneration of forests in floodplain areas (Dufour and Piegay, 2008), plant diversity in wetlands …”
Section: Examples Of Threshold Behaviour In Hydrology and Earth Systementioning
confidence: 99%
“…Fraxinus is a flexible genus which can be found over a wide range of growing conditionsfrom coastal to mountainous regions, especially on steep slopes (Stöhr & Lösch, 2004), from pioneer to mature woodland, from nutrient-rich to poorer soils (Ferrazzini et al, 2007;Dufour & Piégay, 2008). Its drought tolerance and frost sensitivity would have made ash a tree species potentially favored by the expected climate warming and drying (Scherrer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%